1998
DOI: 10.1677/joe.0.1560379
|View full text |Cite
|
Sign up to set email alerts
|

In vivo stimulation of the beta(2)-adrenergic pathway increases expression of the Gi proteins and the alpha(2)A-adrenergic receptor genes in the pregnant rat myometrium

Abstract: Cross-regulations between G s and G i mediated pathways controlling the adenylyl cyclase activity have been clearly demonstrated in vitro. To elucidate whether activation of the -adrenergic pathway in the pregnant myometrium might affect G i proteins and 2 -adrenergic receptors (ARs), we treated late pregnant rats from day 18 to day 21 with twice-daily administration of isoproterenol (8 mg/ kg). This treatment increased myometrial cAMP levels and led after 76 h to a significant and maximal rise in the immunore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 36 publications
(24 reference statements)
2
6
0
Order By: Relevance
“…We therefore examined the responses mediated by ␣ 2 -ARs, which ordinarily act as a negative modulators of AC activity through coupling to G i . We found that stimulation of neonatal hepatic ␣ 2 -ARs potentiated isoproterenol-stimulated cAMP production, an effect previously observed in the fetal liver (1) and in the pregnant rat myometrium (11). Neonatal terbutaline treatment did not alter this pattern.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…We therefore examined the responses mediated by ␣ 2 -ARs, which ordinarily act as a negative modulators of AC activity through coupling to G i . We found that stimulation of neonatal hepatic ␣ 2 -ARs potentiated isoproterenol-stimulated cAMP production, an effect previously observed in the fetal liver (1) and in the pregnant rat myometrium (11). Neonatal terbutaline treatment did not alter this pattern.…”
Section: Discussionsupporting
confidence: 70%
“…Effects of terbutaline on the liver. Neonatal terbutaline had a much greater effect on hepatic ␤-AR binding than on cardiac ␤-ARs (treatment ϫ tissue, P Ͻ 0.0001; [11][12][13][14]. Despite the marked decline in ␤-ARs, the ability of isoproterenol to stimulate AC activity was only slightly reduced (10-15%), an effect clearly distinguishable from the robust receptor downregulation (treatment ϫ measure, P Ͻ 0.0001).…”
Section: Development Of Control Ratsmentioning
confidence: 99%
“…Using immunoblotting studies, we first established that isoproterenol treatment increases Gi2␣ and Gi3␣ levels in myometrial membranes. Previous results from our laboratory demonstrated that this increase results from transcription rate activation of both genes [38]. Upregulation of Gi expression after activation of the ␤-adrenergic pathway was also reported in myocardium [12,39] as well as in in vitro models [11,13].…”
Section: Discussionsupporting
confidence: 53%
“…The interplay between these two ARs is important for maintaining homeostasis of various physiological mechanisms and, in some cases, causing the manifestation of pathophysiological conditions. In peripheral tissues, α 2 and β‐ARs play important roles in modulating uterine smooth muscle tone (Lécrivain et al ., 1998), insulin release from pancreatic islet cells (John et al ., 1990), cytokine release (Kalinichenko et al ., 1999) and vasomotor tone. In addition, neuronal α 2 ‐ and β 2 ‐ARs play an important role in the modulation of noradrenergic neurotransmission in the human CNS and PNS.…”
Section: Introductionmentioning
confidence: 99%